UK Teaching Quality Under the Microscope: What are the Drivers? - Middlehurst, Robin (International Higher Education, 2016)
Under the newly elected government in the UK (May 2015), sweeping changes to quality assurance and the regulatory system for higher education are proposed in England. Proposals include a new emphasis on ‘teaching excellence’ to balance a long-term emphasis on measuring ‘research excellence’ and further marketization. The UK higher education system has had a strong reputation for quality over decades, so international observers may speculate on the rationale for the government’s proposals. This article explores some of the underlying political, economic and social drivers behind the government’s proposals.